Sales And Inventory System For Maperow Store - Azmi, Amir Idlan (Applied Information Technology And Computer Science, 2022)
Abstract: Sales and Inventory System for Maperow Store is a system to facilitate the storage of inventory of goods and sales. Nowadays, sellers have problems in storing and managing their sales data because previously, sales results were recorded manually using traditional methods by writing on paper. As a result, sales data is insecure and easily corrupted or lost. This is because most businesses do not have a system that manages such sales data. Seeing the weakness in the problem then the sales and inventory system in Maperow store was developed. Through this system the seller will be able to get information about the stock of goods clearly and easily. The methodology used in developing this system is the waterfall model where this model is easier to understand when to develop this system. The programming languages used are Hypertext Preprocessor (PHP) and Hypertext Mark-up Language (HTML) and this system is also developed using MySQL database. This system provides online concept that can be used anywhere by users. This will bring a lot of facilities to shopkeepers as they conduct business dealings with customers as well improve the buying experience to customers. It will quickly increase productivity store because it shortens and simplifies the whole process ordering and booking the items. This system is expected to make it easier for sellers to manage the updating of goods, record sales and manage the sale of goods in a more organized and faster.